Hippo pathway effectors YAP1/TAZ induce an EWS–FLI1‐opposing gene signature and associate with disease progression in Ewing sarcoma. Issue 4 (4th February 2020) - Rodríguez‐Núñez, Pablo; Romero‐Pérez, Laura; Amaral, Ana T; Puerto‐Camacho, Pilar; Jordán, Carmen; Marcilla, David; Grünewald, Thomas GP; Alonso, Javier; de Alava, Enrique; Díaz‐Martín, Juan
Abstract: YAP1 and TAZ (WWTR1) oncoproteins are the final transducers of the Hippo tumor suppressor pathway. Deregulation of the pathway leads to YAP1/TAZ activation fostering tumorigenesis in multiple malignant tumor types, including sarcoma. However, oncogenic mutations within the core components of the Hippo pathway are uncommon. Ewing sarcoma (EwS), a pediatric cancer with low mutation rate, is characterized by a canonical fusion involving the gene EWSR1 and FLI1 as the most common partner. The fusion protein is a potent driver of oncogenesis, but secondary alterations are scarce, and little is known about other biological factors that determine the risk of relapse or progression. We have observed YAP1/TAZ expression and transcriptional activity in EwS cell lines. Analyses of 55 primary human EwS samples revealed that high YAP1/TAZ expression was associated with progression of the disease and predicted poorer outcome. We did not observe recurrent SNV or copy number gains/losses in Hippo pathway‐related loci. However, differential CpG methylation of the RASSF1 locus (a regulator of the Hippo pathway) was observed in EwS cell lines compared with mesenchymal stem cells, the putative cell of origin of EwS. Hypermethylation of RASSF1 correlated with the transcriptional silencing of the tumor suppressor isoform RASFF1A, and transcriptional activation of the pro‐tumorigenic isoform RASSF1C, which promotes YAP1/TAZ activation. Knockdown of YAP1/TAZ decreased proliferation and invasion abilities of EwS cells and revealed that YAP1/TAZ transcription activity is inversely correlated with the EWS–FLI1 transcriptional signature. This transcriptional antagonism could be explained partly by EWS–FLI1‐mediated transcriptional repression of TAZ. Thus, YAP1/TAZ may override the transcriptional program induced by the fusion protein, contributing to the phenotypic plasticity determined by dynamic fluctuation of the fusion protein, a recently proposed model for disease dissemination in EwS. © 2019 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.